2012
DOI: 10.1111/j.1464-5491.2012.03669.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin initiation and management in people with Type 2 diabetes in an ethnically diverse population: the healthcare provider perspective

Abstract: The challenge for healthcare providers is to how to address the tension between the optimal clinical time for commencing insulin therapy and the time when the patient feels psychologically ready. To help make these two time points coincide, our findings suggest the need to adopt a holistic approach involving consideration of the cultural context of patients, including their ethnic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 19 publications
1
49
0
1
Order By: Relevance
“…People from Asian cultures also may see the initiation of insulin as indicative of a failure of the patient to care for him- or herself rather than as a result of the natural progression of diabetes. Members of these populations also may believe insulin causes more complications in the long term (12,14,15,22). Similarly, the underutilization of insulin in African Americans is linked to a perception that insulin causes organ damage (9,23).…”
Section: Barriers To the Use Of Insulinmentioning
confidence: 99%
See 2 more Smart Citations
“…People from Asian cultures also may see the initiation of insulin as indicative of a failure of the patient to care for him- or herself rather than as a result of the natural progression of diabetes. Members of these populations also may believe insulin causes more complications in the long term (12,14,15,22). Similarly, the underutilization of insulin in African Americans is linked to a perception that insulin causes organ damage (9,23).…”
Section: Barriers To the Use Of Insulinmentioning
confidence: 99%
“…For example, certain Asian cultures view insulin as a form of handicap that may indicate severe illness and feel it may prevent a person with diabetes from finding a marriage partner (22). Some Asians also are more likely to be influenced by other people’s views about taking injections; this can prompt requests to their HCP to change their therapy even if the change is not as effective at controlling glucose (12). …”
Section: Barriers To the Use Of Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is evidence [6,7] of comparatively lower prescribing of insulin for people with Type 2 diabetes who are from South Asian populations than for the white British population. Whilst not much is known from a South Asian perspective about the reasons for lower levels of prescribing insulin, our previous study of healthcare professionals' views and experiences found that patient-related barriers to insulin prescribing are perceived to be accentuated in some South Asian patients [8]. The reasons cited included lower levels of understanding and knowledge about diabetes and insulin; language barriers; and the influence of 'other people' in decisions about commencing insulin therapy [8].…”
mentioning
confidence: 99%
“…Whilst not much is known from a South Asian perspective about the reasons for lower levels of prescribing insulin, our previous study of healthcare professionals' views and experiences found that patient-related barriers to insulin prescribing are perceived to be accentuated in some South Asian patients [8]. The reasons cited included lower levels of understanding and knowledge about diabetes and insulin; language barriers; and the influence of 'other people' in decisions about commencing insulin therapy [8].A useful concept to emerge from research into the reasons for delays and refusal to commence insulin therapy is 'psychological insulin resistance', which can apply to both healthcare professionals and patients [9,10]. The concept encompasses issues such as fear of needles and feelings of personal failure in patients, and lack of confidence to initiate insulin [11] and concerns about hypoglycaemia in healthcare professionals [12].…”
mentioning
confidence: 99%